Air-Air : Celebrating inflatables. - Doswald, Christoph; Falzon, Laurence; Maniaque, Caroline; Tenret, Yves (s.l. : Grimaldi Forum Monaco : Le 27e stratagème & Inflate-unit-research, 2000)
Inflate-Studio ; Sato, Risa ; Fleury, Sylvie ; Parreno, Philippe & Cattelan, Maurizio ; Reimer, Pierre ; Reinoso, Pablo ; Rockenschaub, Gerwald ; Jeong-Hwa, Choi ; Kusama, Yayoï ; Müller, Hans-Walter ; Blazy, Michel ; Mottura, Angelo ; Crasset, Matali ; Okamoto, Naoko ; Zoritchak, Thomas ; Stucky, Sidney ; Poulain, Guillaume ; Golz, Dorothée ; Decker, Simone ; Bul, Lee ; Kasahara, Izuru ; Courrèges ; Creed, Martin ; Nakamura, Tetsuya ; Leroi, David & Blanc-Bernard, Elisa ; Hybert, Fabrice ; Hemmert, Hans ; Barclay, Per ; Rousseaud, Bruno ; Lang & Baumann ; Höller, Carsten ; HAha ; Le Gentil Garçon ; Moriceau, Jean-François & Mrzyk, Petra ; Gygi, Fabrice ; Murakami, Takashi ; Merrick, Thom ; Lavier, Bertrand ; Warhol, Andy ; Peinado, Bruno ; Quentin, Bernard ; Khanh, Quasar ; G.R.A.M. ; Signer, Roman ; Agoston, Serge ; Yanobe, Kenji ; Cercle Ramo Nash ; Perez, Javier ; Tiraboschi, Pascale ; Jacob, Wendy ; David, Jean-Pierre ; van Beirendonck, Walter ; Guillaumon, Jean-Claude ; Durand, Philippe ; Ruiz de Azua, Martin ; Santachiara, Denis ; Agoston, Serge ; Coindet, Delphine ; Höller, Carsten ; Joseph, Pierre ; Crasset, Matali ; Ragot, Christian ; Kippenberger, Martin ; Pesce, Gaetano ; Blanc, Jean-Luc ; Detourne, Nathalie ; Hattan, Eric ; Atrux-Tallau, Laurette ; Ramette, Philippe ; Lacombe, Bertrand & Dejode, Sophie ; Moulin, Xavier & Kohama, Izumi ; Koenig, Anakin ; Barré, Virginie ; POD
Air-Air, Grimaldi Forum de Monaco, Monaco, 21 juillet au 27 août 2000
boek